The Spending Equation: Unpacking Remittances, GDP, and CPI in Nepal’s Private Consumption (Management Dynamics, 2023)
This study examines the determinants of private consumption in Nepal, focusing on remittances, GDP, and inflation. Private consumption plays a critical role in economic growth, yet its drivers in Nepal remain underexplored, particularly concerning cross-border inflation impacts. Utilizing an ARDL framework, the study analyzes time-series data from 1975–2023. Unit root and F-Bounds tests were employed to ensure stationarity and confirm long-run relationships among variables. The Error Correction Model (ECM) captured short-run dynamics and adjustment speeds. Diagnostic tests ensured model robustness and stability. The findings reveal significant positive long-run effects of remittances (coefficient: 0.0256) and GDP (coefficient: 0.0433) on private consumption. Inflation exhibits mixed impacts, with Indian inflation negatively affecting consumption. The ECM demonstrated a rapid adjustment speed (−1.0095), indicating strong reversion to equilibrium. Diagnostic tests confirmed model stability and robustness. The results align with Keynesian theory, emphasizing income’s role in consumption, and highlight the novelty of incorporating cross-border inflation dynamics. The findings emphasize the need for policies stabilizing remittance inflows, promoting inclusive growth, and managing inflation. This study offers novel insights into the interconnectedness of macroeconomic variables and provides a framework for future research on consumption behavior in Nepal.